LearningMu: English web-based learning media to assist students self-learning - Haiyudi Haiyudi; Supayuandi Pratama; Anggun Aprilliana; Nadya Listyaningrum Norkhasanah (English Language Education Study Program, Teacher Traning and Education Faculty, Universitas Muhammadiyah Cirebon, 2025)
English learning requires not only engaging instruction but also meaningful learning experiences. However, some persistent challenges remain, such as a lack of innovative teaching strategies and insufficient opportunities for students to actively use the language. This study aims to develop LearningMu, a web-based English learning platform designed to transform teacher-centered instruction into student-centered learning. The platform also aims to improve students’ interest, engagement, and language proficiency through an enjoyable and contextualized learning process. This research adopts a Research and Development (R&D) approach using the ADDIE model, although it is currently limited to the trial stage. The trial was conducted through feasibility testing, involving both validation and practicality assessments, carried out at SMA Muhammadiyah Belitung. Data were collected through interviews, document analysis, and questionnaires, and analyzed using a quantitative descriptive approach by comparing the outcomes to existing feasibility standards. The results show that LearningMu achieved a validity score of 4.05 and a practicality score of 3.72 (on a 5-point scale), indicating that the product is both valid and practical for classroom implementation. Although the initial results are promising, further development and refinement are still needed to maximize the effectiveness of LearningMu and enhance its applicability in broader educational settings. Keywords: web-based learning; English education; learning media; independent learning